LCA evaluation for the hydrogen production from biogas through the innovative BioRobur project concept. (11th May 2017) - Battista, F.; Montenegro Camacho, Y.S.; Hernández, S.; Bensaid, S.; Herrmann, A.; Krause, H.; Trimis, D.; Fino, D.
Abstract: BioRobur is a project aimed to produce hydrogen from biogas through an auto-thermal reforming (ATR) process, in which innovative catalytic systems are used to promote the ATR reactions involved in the process for the conversion of biogas into syngas. A detailed LCA study of hydrogen production from biogas ATR using the BioRobur technology has been performed. LCA analysis has been also conducted for other two conventional processes for the production of hydrogen from biogas: the steam reforming and water hydrolysis (a biogas-fueled Internal Combustion engine (ICE) followed by an Electrolyser). A comparison between these technologies has been made from both the environmental and the energetic viewpoints. The LCA has demonstrated that BioRobur is the most environmentally friendly of considered processes. Moreover, the ICE plus Electrolyser has resulted to be the because of the very large amount of biogas needed for the least efficient process, due to the low conversion yield of biogas into energy of the ICE. Graphical abstract: Highlights: Detailed LCA of different technologies for conversion of biogas into H2 . The ATR-based BioRobur process is the most sustainable and energy efficient. The ATR process has ∼4% GWP and 5% GER less than a biogas-fed SR process. IC engines with alkaline electrolyser is the least efficient and sustainable process.